Pregnant girl : a story of teen motherhood, college, and creating a better future for young families - Lewis, Nicole Lynn, 1980- (Beacon Press, 2021)
"A teen mother's intimate, fearless account of America's damaging response to teen pregnancy, the systemic issues that exacerbate it, the insurmountable barriers to college for parenting students, and a blueprint for helping young families overcome the odds"--